Development, characterization and storage stability of banana-peanut candy bar - Lamberto, Phareza Moreño (Miagao, Iloilo School of Technology, U. P. in the Visayas, 2007)
Four formulations of banana-peanut candy bars were prepared.
Sotech thesis.
Keywords: Banana-peanut candy bars